Geomorfogênese dos degraus escalonados do sudeste de Minas Gerais - Breno Ribeiro Marent (2016)
The relief of the south-eastern area of Minas Gerais is organised, according to the literature, in staggered steps. Situated among these steps, the Great Escarpment, constitutes na important divide between the oceanic basins and the continental interior, the origin of which is related to the opening up of the South Atlantic Ocean. These staggered surfaces suggest that the development of the hydrographic network occurred through processes of degradation of the coastal basins adjusted to differing baseline levels over time, as a result of meso-cenozoic tectonic activity, through the vertical incision of the drainage network accompanied by the lateral retraction of the craggy edges. In this context, the aim of this study is to present and discuss the processes and mechanisms involved in the evolution of the hydrographic network adjacent to the Brazilian continental margin. In seeking to investigate how these steps are linked to the regional geomorphological configuration, it was necessary to perform an analysis on a larger snippet, but in association with more detailed spatial scales. In order to arrive at the construction of the conceptions underpinning this work, it was necessary to adopt a series of procedures, beginning with analysis of the relief, within which geomorphological compartmentation of the investigated area was carried out, recognizing and demonstrating the existence of the staggered steps in clear conformity with the hydrographic network, in both plan and profile. The compartmentation unfolded during the investigation of topographic ruptures and supplied, initially, a perspective on three spatial scales regional, sub-regional and local. On the regional scale, dissection of the relief was shown to play an important role in the establishment of two great geomorphological domains (coastal and interior), divided by the Great Escarpment. On the sub-regional scale, the staggered steps structure inside these compartments was revealed to be under significant structural and tectonic conditioning. On the local scale the lithology was identified as defining the geomorphological landscape, as with the rocky outcrops. These analyses demanded investigation of the drainage, the organization of which demonstrated general baseline level control in the oceanic compartment and the local base level controlling the denudation of the interior compartment, on the regional scale. Besides this, on the sub-regional scale, local baseline levels control the denudation between the coastal basins and are responsible for ruptures in the drainage closely associated with the tectonic organization of these basins. On the local scale, in investigating the geomorphological scenarios of the craggy edges, structural control was observed which, at times, overlaps with the regional control (NE-SW). In these scenarios, the drainage and relief organized according to the oldest morphogenesis have been substituted by new landscape through the process of evolution of the Great Escarpment, under clear structural control. This influences in the direction of the drainage at the craggy edges and is reflected in the formation of hanging valleys. The association of this set of elements to secondary data and the processing of images using geoprocessing made possible the elaboration of an initial approximation to the evolutionary schemes of the relief. These schemes observed from a multi-scale perspective support interpretations of the landscape through the joint action of backwearing and downwearing, due to the propagation of knickpoints on the craggy edges and to the predominance of the vertical incision along the steps.